The Herbal Potential of Ginger (Zingiber officinale Roscoe) and Guava (Psidium guajava L.) as Supplements for the Management of Coronavirus Disease 2019 (COVID-19) - Rachmat Hidayat; Patricia Wulandari (Eureka Herba Indonesia, 2023)
Increasing the body's immunity is one of the efforts to prevent infection with COVID-19. This literature review aims to describe the potential of ginger (Zingiber officinale roscoe) and guava (Psidium guajava L.) as supplements for the management of COVID-19. Grated ginger (Zingiber officinale roscoe) is used as a topical medication to treat swelling, rheumatism, and headaches. In vivo tests in rats that were immunosuppressed using cyclophosphamide showed that ginger essential oil given once a day orally for a week could increase the humoral immune response. Meanwhile, guava has high levels of polyphenols such as myricetin and apigenin compounds, ellagic acid, and anthocyanins. The high vitamin C content in guava contributes to immune defense by supporting various cellular functions of both the innate and adaptive immune systems.